Tinjauan Teologis Tentang Pendidikan Kristiani Multikultural - Hery Susanto (Sekolah Agama Kristen Terpadu Pesat Salatiga, 2021)
Multicultural Christian education is in line with the diversity that exists in Indonesia. Theologically, Christian education contains elements of knowing God which is universal so that it is not only controlled by the Jews. In the Jewish tradition Christian education was intense, but Jesus extended that teaching beyond the boundaries of Jewish culture and tradition. The culture used is the culture of God's kingdom that puts forward the power of God's government in the world and heaven. In every human culture, there is always room for religiosity, and that is what must be taught. The Lord Jesus teaches anyone to be able to know God's Kingdom and His will in human culture. The method used is a literature qualitative research method by comparing various sources of writing related to multicultural Christian education and its implementation in Christian education in Indonesian culture.AbstrakPendidikan kristiani multikultural sangat sesuai dengan keberagaman yang ada di Indonesia. Secara teologis, pendidikan Kristiani mengandung unsur pengenalan akan Tuhan yang universal sehingga bukan hanya dikuasai oleh orang Yahudi saja. Dalam tradisi Yahudi pendidikan kristiani sangan intens, tetapi Yesus mengembangkan pengajaran itu melampaui batasan budaya dan tradisi Yahudi. Budaya yang digunakan adalah budaya kerajaan Allah yang lebih menekankan kuasa pemerintahan Allah di dalam dunia dan di surga. Setiap budaya manusia selalu memberi ruang bagi religiusitas, dan itulah yang harus diajarkan. Tuhan Yesus mengajarkan kepada siapapun untuk dapat mengenal Kerajaan Allah dan kehendak-Nya dalam budaya manusia. Metode yang digunakan adalah metode penelitian kualitatif literature dengan membandingkan berbagai sumber tulisan yang terkait dengan pendidikan kristiani multikultur dan implementasinya dalam pendidikan kristiani dalam budaya masyarakat Indonesia.